Logistics Structure Analysis for Selayar Tangerine Supply Chain Mapping - Ahmad, Ilham; Rahmaniar; Jassin, Ernawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Citrus fruits are in demand not only for their freshness, but also for their fiber content as nutrients and vitamins, especially vitamin C and vitamin A, which are beneficial for health. Selayar Islands Regency is a citrus development area in South Sulawesi Province. The citrus crop developed in Selayar Islands Regency is the tangerine variety. Along with the development of the citrus plant area, the population of citrus plants in Selayar Islands Regency increases every year. This study aims to describe the mapping of the Selayar tangerine supply chain structure through logistics cost analysis to map the distribution of income between supply chains. The number of respondents in this study was 45 people. This research uses descriptive analysis with convenience and snowball sampling methods to get an objective picture. This research uses logistics cost analysis using the Activity Based Costing method. The results showed that the levels involved in the supply chain are farmers, collectors, wholesalers, small traders, and consumers. The results of the logistics cost calculation show material handling costs as the highest cost of the entire Selayar tangerine supply chain cost.